BAGAIMANA TURNOVER INTENTION GENERASI MILLENIAL DAN NON MILLENIAL DIPENGARUH MEANING OF WORK DAN JOB SATISFACTION (STUDI PADA BAGIAN ADMINISTRASI PTS A, JAKARTA) - Petrus Satrio Hananto Wibisono (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
This study was conducted with the aim to determine the effect meaning of work on intention turnover can be mediated job satisfaction at the administrative staff of the PTS A Jakarta. Sampling method used is random sampling by using a sample of 80 employees of the PTS A, Jakarta. Methods Data analysis used in this study is path analysis with macro software and SPSS 22 for windows Preacher-Hayes 2013 Moderate Mediation Model. The result of this research shows that the meaning of work can decrease the intention turnover through job satisfaction at the administrative staff at PTS A Jakarta. Significant work meanings increase job satisfaction. Significant job satisfaction towards turnover intention.